2016
DOI: 10.1158/1535-7163.mct-15-0606
|View full text |Cite
|
Sign up to set email alerts
|

Induction of miR-137 by Isorhapontigenin (ISO) Directly Targets Sp1 Protein Translation and Mediates Its Anticancer Activity BothIn VitroandIn Vivo

Abstract: Our recent studies found that isorhapontigenin (ISO) showed a significant inhibitory effect on human bladder cancer cell growth, accompanied with cell cycle G0/G1 arrest as well as down-regulation of Cyclin D1 expression at transcriptional level via inhibition of Sp1 transactivation in bladder cancer cells. In current studies, the potential ISO inhibition of bladder tumor formation has been explored in xenograft nude mouse model, and the molecular mechanisms underlying ISO inhibition of Sp1 expression and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 51 publications
(72 reference statements)
5
43
0
Order By: Relevance
“…It has been shown that Sp1 acts as a tumor suppressor to suppress colorectal cancer growth and metastasis by increasing miRNA‐52d‐5p transcription for target CTHRC1 (Yan et al ., ). We have reported that the anti‐cancer drug ISO downregulates Sp1 translation to block BC cell growth and IHC‐P results show Sp1 is upregulated in BBN‐induced BC tissues, suggesting an oncogenic role of Sp1 in BC (Zeng et al ., ). Here, we further reveal that Sp1 bound directly to the mmp‐2 promoter and increased its transcription, promoting bladder cancer cell invasion.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that Sp1 acts as a tumor suppressor to suppress colorectal cancer growth and metastasis by increasing miRNA‐52d‐5p transcription for target CTHRC1 (Yan et al ., ). We have reported that the anti‐cancer drug ISO downregulates Sp1 translation to block BC cell growth and IHC‐P results show Sp1 is upregulated in BBN‐induced BC tissues, suggesting an oncogenic role of Sp1 in BC (Zeng et al ., ). Here, we further reveal that Sp1 bound directly to the mmp‐2 promoter and increased its transcription, promoting bladder cancer cell invasion.…”
Section: Discussionmentioning
confidence: 97%
“…The total cell microRNAs and human bladder tissue microRNAs were extracted using the miRNeasy Mini Kit (Qiagen, Valencia, CA, USA) as described in our previous studies [45,46]. Total RNA (1 μg) was used for reverse transcription, and analysis of miR-7, miR-17, miR-23a, miR-24, miR-93, miR-129, miR-137, miR-200c, and miR-214 expression were determined by the 7900HT Fast Real-time PCR system (Applied Biosystems, Carlsbad, CA, USA) using the miScript PCR kit (Qiagen, Valencia, CA, USA).…”
Section: Quantitative Rt-pcr For Mirna Assaymentioning
confidence: 99%
“…The control inserts without Matrigel and invasion kit were purchased from BD Falcon; the invasion assay was performed according to the manufacturer's instruction in normal cell culture serum as described in our previous studies [18,45]. The cells were seeded in the inserts both with and without Matrigel.…”
Section: Cell Migration and Invasion Assaymentioning
confidence: 99%
“…Several studies have shown that among the potential causes for BC, there are a variety of molecular factors such as noncoding RNAs (10)(11)(12)(13)(14)(15). Included in the latter are microRNAs (miRNAs), a class of small noncoding RNAs that regulate gene protein expression by repressing protein translation or by affecting mRNA stability through binding to its specific target sequences.…”
mentioning
confidence: 99%
“…A growing collection of evidence has demonstrated that miRNAs play important roles in regulating growth and invasion, as well as chemo-sensitivity of different types of cancers. Several miRNAs have been verified as contributing to BC cell metastasis and proliferation (10)(11)(12)(13). However, precise mechanisms underlying how these miRNAs act in BC are poorly defined.…”
mentioning
confidence: 99%